2018
DOI: 10.1007/s11427-017-9269-8
|View full text |Cite
|
Sign up to set email alerts
|

GPR54 deficiency reduces the Treg population and aggravates experimental autoimmune encephalomyelitis in mice

Abstract: GPR54 is highly expressed in the central nervous system and plays a crucial role in pubertal development. However, GRP54 is also expressed in the immune system, implying possible immunoregulatory functions. Here we investigated the role of GPR54 in T cell and immune tolerance. GPR54 deficiency led to an enlarged thymus, an increased number of thymocytes, and altered thymic micro-architecture starting around puberty, indicating GPR54 function in T-cell development through its regulatory effect on the gonadal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…As kisspeptin regulated Treg cells in the spleen and uterus of mice, its specific mechanism was investigated. A study has previously confirmed the expression of GPR54 in CD4 + T cells of mouse thymus and spleen 16 . Therefore, whether GPR54 could be expressed on Treg cells, allowing them to bind to kisspeptin and exert its effects, was explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As kisspeptin regulated Treg cells in the spleen and uterus of mice, its specific mechanism was investigated. A study has previously confirmed the expression of GPR54 in CD4 + T cells of mouse thymus and spleen 16 . Therefore, whether GPR54 could be expressed on Treg cells, allowing them to bind to kisspeptin and exert its effects, was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Kisspeptin/GPR54 has been observed to inhibit the function of CD8 + T cells and promote lung cancer progression 15 . Furthermore, GPR54 −/− mice have been found to exhibit a reduced proportion of CD4 + FOXP3 + Treg cells and develop a more severe form of experimental autoimmune encephalomyelitis 16 . Hence, kisspeptin is crucial for immune modulation, but its specific mechanism in the pathogenesis of RSA remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological inhibitors of the inflammasome pathway have broad therapeutic potential for the treatment of diseases that involve activation of this process [ 21 , 22 , 27 , 29 ]. Moreover, previous studies have demonstrated the immunomodulatory activity of kisspeptin on monocytes, neutrophils, and regulatory T lymphocytes [ 34 , 35 , 36 ]. However, there is no information on whether kisspeptin is also capable of modulating the activation of the inflammasome-NLRP3 pathway and pyroptosis.…”
Section: Introductionmentioning
confidence: 99%